Hypertension in Chronic Kidney Disease: An Update on Diagnosis and Management. Issue 2 (February 2023) - Gupta, Ankur; Nagaraju, Shankar Prasad; Bhojaraja, Mohan V.; Swaminathan, Shilna Muttickal; Mohan, Pooja Basthi
Abstract : This review includes the latest guidelines that have significantly changed the diagnosis as well as the management of hypertension in patients and special populations with chronic kidney disease. Moreover, previous reviews on this topic do not cover any guidelines on management. Because the majority of these patients are being managed in the community hospitals by internists, this review is likely to add to their knowledge in improving outcomes in this population subgroup. Abstract: Hypertension (HTN) and chronic kidney disease (CKD) are pathophysiologic states that are intimately related, such that long-term HTN can lead to poor kidney function, and renal function decline can lead to worsening blood pressure (BP) control. HTN in CKD is caused by an interplay of factors, including salt and water retention, with extracellular volume expansion, sympathetic nervous system overactivity, renin-angiotensin-aldosterone system activation, and endothelial dysfunction. BP variability in the CKD population is significant, however, and thus requires close monitoring for appropriate management. With accumulating evidence, the diagnosis as well as management of HTN in CKD has been evolving in the last decade. In this comprehensive review based on current evidence and recommendations, we summarize the basics of pathophysiology, BP variability, diagnosis, and management of HTN in CKD with an emphasis on special populations with CKD.